Analisis Kualitas Layanan pada Aplikasi Mobile JKN dengan Tingkat Kepuasan Pengguna Mobile JKN BPJS Kesehatan di Kabupaten Demak - Rohmah, Saidatur; Desty, Rani Tiara; Arumsari, Wahyuni (Indonesian Journal of Health Community, 2024)
Demak Regency is part of the working area of BPJS Kesehatan Semarang Branch with a service usage rate of 86.96% in March 2022. The purpose of this study is to analyze the relationship between the quality of JKN mobile application services with the satisfaction of JKN BPJS Kesehatan mobile users in Demak Regency. This research method uses a quantitative approach with a cross-sectional type to analyze the relationship between JKN mobile application service quality and user satisfaction in Demak Regency. The data analysis technique uses univariate and bivariate analysis with the Chi-square test. The results showed that there was a relationship between the quality of service on the JKN mobile application and the satisfaction of JKN BPJS Kesehatan mobile users in Demak Regency which included the following components: efficient (Efficiency) with a p-value of 0.002<0.05; fulfillment (fullfilment) p-value 0.002<0.05; System Availability p-value 0.004<0.05; Privacy P-value 0.000<0.05 responsiveness p-value 0.001<0.05; compensation p-value 0.032<0.05; contact p-value 0.319>0.05. Of the 7 dimensions, only the contact dimension has no relationship with the satisfaction of JKN BPJS Kesehatan mobile users because the value is >0.05. The overall percentage of user satisfaction is 80%. It can be concluded that to increase the satisfaction value of JKN mobile users, the quality of service in the box dimension needs to be improved.